Gestures in Contemporary Music Performance: A Method to Assist the Performer's Artistic Process. Issue 4 (2nd September 2016) - Caruso, Giusy; Coorevits, Esther; Nijs, Luc; Leman, Marc
Abstract : In this paper, we propose a method to assist a performer in dealing with the challenges of contemporary music performance. Such a method aims at making a performer's artistic process (which is based on cognitive and sensorimotor schemes) more explicit, in order to better understand the relationship between goals, actions, and sounds. The method does not provide a heuristic that will automatically lead to a new performance model. Rather, it is meant to assist performers in (re)framing their interpretative outlooks while rendering their performative code explicit with the help of innovative mirror-like technologies. First we provide a general framework for understanding music performance, based on the notion of performance spaces and frames, and on recent insights in embodied interactions with music. Next we elaborate on how to approach the development of such understanding through performance research. Then we apply this framework to the performance of contemporary music, describing two complementary analysis approaches, in which we focus on analysis from a third-person perspective, and from a first-person perspective, respectively. The paper concludes with a discussion about the method and its value for both research and performance.